HUBUNGAN ANTARA TEKSTUR TANAH DENGAN KADAR FOSFAT, KALIUM DAN KAPASITAS TUKAR KATION TANAH DARI BEBERAPA CONTOH TANAH DI BALI - NARKA, I WAYAN (AGRITROP, 2012)
A laboratory experiment about correlation of texture (sand, silt and clay fractions) to phosphate (P), potassium (K) content and Cation Exchange Capacity (CEC) of soil was carried out at Soil Laboratory Faculty of Agriculture Udayana University in May until October 2006. Soil samples were taken from regencies of Bali and analyzed some properties of soil such as: soil texture, potassium, available P content and CEC of soil. Soil texture was analyzed with pipet method, potassium content with Bray I method, available P content with Bray I method and CEC with NH4OAc.saturation method. Pearson correlation method was used in this experiment to study the correlation of sand, silt and clay fractions to potassium, available P content and CEC of soil. The result of the experiment showed that, there are highly significant correlation between sand fraction and potassium, available P content and CEC of soil with coefficient correlation (r) of : -0,427**, -0,314* and -0,719** , respectively. Correlation between clay fraction and potassium content, CEC of soil with coefficient correlation (r) of : 0,430** and 0,661**, respectively. Between silt fraction and potassium, available P content and CEC of soil were not significant correlation, with coefficient correlation (r) : 0,127; 0,257 and 0,256, respectively . Between potassium content and CEC of soil showed a highly significant correlation with coefficient correlation (r) = 0,383**. Step wise analyzed showed that , potassium content was significantly influenced by clay fraction, while available P and CEC of soil were significantly affected by sand
Keywords: soil texture, phosphate, potassium, CEC